Effect of direct renin inhibition on vascular function after long-term treatment with aliskiren in hypertensive and diabetic patients. Issue 1 (January 2021) - Savoia, Carmine; De Ciuceis, Carolina; Paini, Anna; Carletti, Raffaella; Arrabito, Emanuele; Nicoletti, Carmine; Mercantini, Paolo; Di Gioia, Cira; Battistoni, Allegra; Ucci, Sarassunta; Filippini, Antonio; Agabiti Rosei, Enrico; et al.
Abstract : Objective: We tested the hypothesis that chronic treatment with the direct renin inhibitor aliskiren improves vascular function in resistance and conduit arteries of type two diabetic and hypertensive patients. Method: Sixteen patients with mild essential hypertension and with a previous diagnosis of noninsulin-dependent diabetes mellitus were included in the study. Patients were then randomized to aliskiren (150 mg once daily, n  = 9), or ramipril (5 mg once daily, n  = 7). Each patient underwent a biopsy of the subcutaneous tissue and small arteries were dissected and mounted on a pressurized micromyograph to evaluate endothelium dependent vasorelaxation in response to acetylcholine ±  N omega-nitro-L-arginine methyl ester hydrochloride in vessels precontracted with norepinephrine. Endothelial function has been quantified also in large conduit arteries by flow-mediated dilation. Results: A similar office blood pressure-lowering effect was observed with the two drugs, although changes in DBP were not statistically significant in the ramipril group. Aliskiren significantly improved endothelium-dependent relaxation in subcutaneous resistance arteries, as well as increased flow-mediated dilation in conduit arteries, whereas the effects induced by ramipril did not reach statistical significance. Only aliskiren significantly increased the expression of p1177-endothelial nitric oxide synthase in the endothelium. Both aliskiren and ramipril had a negligible effect on markers of oxidative stress. Conclusion: Aliskiren restored endothelial function and induced a more prompt peripheral vasodilation in hypertensive and diabetic patients possibly through the increased production of nitric oxide via the enhanced expression and function of the active phosphorylated form of endothelial nitric oxide synthase.